Relationship between Ureaplasma urealyticum Colonization and Bronchopulmonary Dysplasia in Very Low Birth Weight Premature Infants: A Prospective Cohort Study - Majid Mahallei; Mohmmad Bagher Hosseini; Heidar Esmaili; Golam Reza Asadi (Mashhad University of Medical Sciences, 2019)
Background: Bronchopulmonary dysplasia (BPD) is the second prevalent lung disease and one of the care challenges of premature newborns. Different risk factors play an important role in the development of this disease. Therefore, the aim of the present study was to investigate the relationship between colonization with Ureaplasma urealyticum and BPD. Methods: This prospective cohort study was conducted in 2017 in the neonatal intensive care unit of Alzahra Hospital in Tabriz, Iran. The samples included newborns weighing less than 1500 g with the gestational age of less than 32 weeks who required intubation within 72 h after birth. Following recording the initial information, the secretions within the trachea were aspirated and Ureaplasma urealyticum was detected in reference laboratory by polymerase chain reaction. Afterwards, we completed a follow-up of 28 days after birth for BPD. Results: Our findings demonstrated that out of 82 infants, 21 cases (26.3%) were excluded from the study due to discharge from hospital or death before the age of 28 days. Among the rest (61 newborns), three cases (4.3%) were shown to have secretions infected with Ureaplasma and 33 cases (54.1%) suffered from BPD. All the three newborns infected with Ureaplasma had BPD. However, no significant relationship was observed between Ureaplasma infection and BPD (P=0.24). According to the analysis of data, the most important factors contributing to BPD among the patients were the gestational age and birth weight. In other words, for one week increase in the age of pregnancy and for each 100 g increase in birth weight, the likelihood of BPD is reduced by 55% and 1%, respectively. In the present study, no relationship was found between Ureaplasma infection and BPD, which might be due to the low prevalence of this infection. Nonetheless, prematurity and low birth weight could be regarded as the two considerable risk factors for BPD. Conclusion: In order to perfectly determine the role of bacterial colonization within the trachea in BPD, collecting and analyzing various samples for the existence of other bacteria are recommended.